Cover Image. (27th November 2020) - Salis, Elena; Gerber, Andreas; Andreasen, Jens Wenzel; Gevorgyan, Suren A.; Betts, Tom; Mihaylov, Blagovest; Gottschalg, Ralph; Kodolbaş, Alp Osman; Yilmaz, Okan; Leidl, Roman; Rennhofer, Marcus; Zamini, Shokufeh; et al.
Abstract : The cover image is based on the Research Article A European proficiency test on thin‐film tandem photovoltaic devices by Elena Salis et al., https://doi.org/10.1002/pip.3322 .